Self-Treatment of Posterior Canal Benign Paroxysmal Positional Vertigo: A Preliminary Study - Gan, Zhuangqin; Zhou, Shiling; Yang, Hui; He, Feng; Wei, Dong; Bai, Ya; Wang, Yuanyuan; Wang, Yingxia; Fu, Wei; Han, Junliang (Frontiers in Medicine, 2021)
Objectives: The purpose of this study is to investigate a modified Epley maneuver for self-treatment of posterior canal benign paroxysmal positional vertigo(PC-BPPV). Methods: 155 patients with PC-BPPV were recruited in this study. All patients were randomized to Epley maneuver group(n=77) and modified Epley maneuver group(n=78). The resolution rate(one day and one week), residual symptoms after maneuver and adverse effects were analyzed. Results: It was found that the modified Epley maneuver group had a higher resolution rate than that of Epley maneuver group in treatment of PC-BPPV after one day of the initial maneuver(p<0.05). However, there was no difference of resolution rate between Epley maneuver group and modified Epley maneuver group in resolution rate after one week of the initial maneuver(p>0.05). The modified Epley maneuver group had less residual symptoms than that of Epley maneuver group one week after treatment of PC-BPPV(p<0.05). In addition, significant improvements were observed in average DHI scores in patients who underwent the modified Epley maneuver compared to the Epley maneuver(p<0.05). There was no significance difference in adverse effects between two groups(p>0.05). Conclusions: The modified Epley maneuver has a satisfactory therapeutic efficacy with less residual symptoms and could be recommended as self-treatment for patients with PC-BPPV.